1993
DOI: 10.1111/j.1365-2044.1993.tb06912.x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory assessment of the Baxter disposable patient‐controlled analgesia system

Abstract: SummaryThe performance of the Baxter patient-controlled analgesia infusor system was assessed in the laboratory. The pow of the 5 m1.h-' infusor was measured gravimetrically with the pow restrictor maintained at 31°C and the reservoir at either 20°C or 2YC. At 25°C rhe mean flow was 4.98 (SEM 0.06) ml.h-' and at 20°C the mean p o w was 4.32 (0.05) m1.h-'. The patient-control module performed reliably, delivering a mean of 0.42 (0.001) ml following depression of the button, slighly less than the manufacturer's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The safety and effectiveness of this non-electronic Table 6. Cost of therapy (Belgian Francs) in patient-PCA system has been previously documented (10, controlled analgesia (PCA) infusor treatment and [14][15][16]. Ballantyne et al [17] found that patients treated conventional intramuscular (i.m.)…”
Section: Discussionmentioning
confidence: 99%
“…The safety and effectiveness of this non-electronic Table 6. Cost of therapy (Belgian Francs) in patient-PCA system has been previously documented (10, controlled analgesia (PCA) infusor treatment and [14][15][16]. Ballantyne et al [17] found that patients treated conventional intramuscular (i.m.)…”
Section: Discussionmentioning
confidence: 99%